The painful knee after total knee arthroplasty: evaluation and management - Momoli, Alberto; Giarretta, Stefano; Modena, Martino; Micheloni, Gian Mario (Acta Biomedica Atenei Parmensis, 2017)
Total knee arthroplasty (TKA) is the treatment of choice for end-stage osteoarthritis of the knee. The aging of population and the need to maintain high quality of life have increased the demand for TKA. Although considered a successful procedure, 15-30% of patients presenting persistent pain. The management of these patients requires a clinical, laboratory and radiological assessment in order to address the underlying aetiology. There are several causes of pain, divided in joint and non-joint related, which should be diagnosed and treated promptly. Patients with unexplained pain should be treated conservatively since a plausible reason has been identified.